Transglutaminases in Crohn's disease. Issue 5 (November 1995) - D'Argenio, G; Biancone, L; Cosenza, V; Della Valle, N; D'Armiento, F P; Boirivant, M; Pallone, F; Mazzacca, G
Abstract : Transglutaminases are a family of Ca-dependent enzymes involved in various biological events. Circulating transglutaminase (factor XIIIa) is decreased in blood of patients with inflammatory bowel diseases. There is evidence that factor XIIIa and tissue type transglutaminase, present in cell cytosol, bind to various proteins of the extracellular matrix. This study examined the value of serum transglutaminase assay in the treatment and follow up of Crohn's disease and then investigated the intestinal location of both forms of transglutaminases by immunohistochemistry in normal and abnormal tissues. Serum transglutaminase activity was assayed in 36 patients with active Crohn's disease (CDAI > 150). Eighteen patients were studied prospectively from relapse into remission. A significant inverse correlation (p < 0.001) was found between circulating transglutaminase and Crohn's disease activity index; a correlation was also found between serum transglutaminase and serum orosomucoid (p < 0.01) and C reactive protein (p < 0.01). Patients were prospectively studied until clinical remission showed improvement in both their CDAI score mean (SD) (230 (46) to 72 (34), p < 0.01) and transglutaminase activity mean (SD) (0.61 (0.12) to 0.93 (0.13) mU/ml, p < 0.01). The immunohistochemistry assessment showed a colocalisation of factor XIIIa and tissue transglutaminase to the extracellular matrix of damaged tissues. In conclusion, these data confirm the value of serum transglutaminase assay as marker of Crohn's disease activity, extend the utility of serum transglutaminase assay to follow up of the disease, and emphasised the role of different types of transglutaminases in extracellular matrix assembly in the damaged tissues.